The truth about teaching : what I wish the veterans had told me - Armstrong, Coleen, 1946- (San Francisco : Jossey-Bass, 2009)
"A beautiful gift book that offers encouragement, comfort, and inspiration for new (and veteran) teachers This beautifully designed book is a celebration of the joys and challenges of the teaching life. Author and veteran educator Coleen Armstrong is a wise, witty, and caring mentor. Her words of encouragement will resonate with new teachers, with students in teacher education schools, and with veteran teachers who wish to remember that they are not alone in an often lonely profession. From lesson plans to large classes; salaries to student engagement; germs to geometry-learning (or remembering) to love both the highs and lows of the profession has never been easier, or more fun. Contains a wealth of wise, humorous, and practical advice for all teachers Includes over 150 tips, suggestions, and ideas Co-published with Inspiring Teachers, a teacher-created organization"--Provided by publisher.
"Published in Partnership with Inspiring Teachers ."
Includes bibliographical references and index.
Keywords: Teaching -- United States; First year teachers -- In-service training -- United States